Business perception and change management for the use of virtual reality in an agro-export company - Yarleque Ayala, Lady Di Irene; Cosio Borda, Ricardo Fernando; Ramírez Briones, Lorena; Noriega Monar, Gloria Mercedes; Cajavilca Gonzáles, Berenice (LACCEI, 2024)
The objective of this research was to determine the relationship between business perception and change management for the use of virtual reality in an agro-export company. A methodology applied with a quantitative approach, at a correlational level, was used and a questionnaire for each variable was applied as a data collection instrument. The sample was 136 collaborators. The result of the study was that the correlation between business perception and change management was 0.615, expressing a moderate positive association that was significant. The conclusion of the study indicates a positive relationship between the variables, which means that when there is a favorable business perception for the use of virtual reality, change management will be a process that will develop positively, in a less complex and more efficient way for the agro-export company.